2000
DOI: 10.1063/1.126407
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature minority-carrier injection-enhanced recovery of radiation-induced defects in p-InGaP and solar cells

Abstract: Articles you may be interested inEffects of thermal annealing on deep-level defects and minority-carrier electron diffusion length in Be-doped InGaAsN J. Appl. Phys. 97, 073702 (2005); 10.1063/1.1871334Majority-and minority-carrier deep level traps in proton-irradiated n + /p -InGaP space solar cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
2

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Very recently 1 we have presented a direct observation of minority-carrier injection-enhanced annealing of the dominant radiation-induced hole trap labeled H2 located at 0.51-0.55 eV above the valance band, in p InGaP by deep level transient spectroscopy ͑DLTS͒. However, the mechanism involved in this recombination-enhanced defect reactions remains still an open question.…”
Section: Introductionmentioning
confidence: 97%
“…Very recently 1 we have presented a direct observation of minority-carrier injection-enhanced annealing of the dominant radiation-induced hole trap labeled H2 located at 0.51-0.55 eV above the valance band, in p InGaP by deep level transient spectroscopy ͑DLTS͒. However, the mechanism involved in this recombination-enhanced defect reactions remains still an open question.…”
Section: Introductionmentioning
confidence: 97%
“…Figure 14 shows DLTS spectrum of Trap H2 (Ev+0.55eV) with various time of injection at 25 0 C with an injection density of 100mA/cm 2 . It is also found [26] by DLTS measurement that major defect center H2 (Ev+0.55eV) recover by forward bias or light illumination. Moreover, the H2 center is confirmed to act as a recombination center by using the double carrier pulse DLTS method as shown in Fig.…”
Section: -Mev Electron Fluence (Cm -2 )mentioning
confidence: 91%
“…Figure 7.23 shows DLTS (deep-level transient spectroscopy) spectra of the hole trap H2 (Ev+0.55 eV) for various injection times at 25 • C with a forward bias injection density of 100 mA cm −2 . Khan et al (2000) found from DLTS measurements that this major defect level recovers under forward bias or light illumination, i.e. the defect signal decreases with prolonged light exposure.…”
Section: Radiation Resistance Of Ingap-based Multijunction Solar Cellsmentioning
confidence: 95%